Famine, remittances, and global justice. (September 2022) - Matthew Hoye, J.
Abstract: Famine is not on the global justice theory agenda. Two plausible reasons explain why. First, that global justice theory has moved toward a concern with international justice and reforming existing international organizations and away from what was considered to be a question of global ethics. And second, that famine was influentially identified by Amartya Sen as question of the domestic political economy and thus indeed a domestic justice concern. However, the political economy of famine has changed: it has transnationalised. I argue that famine should be on the global justice theory agenda, but that to do so requires that global justice theory reform itself first. The argument unfolds in three steps. Initially, I diagnose the benefits and constraints of methodological nationalism in famine studies and global justice theorization. I then set out an exploratory case study of the transnationalisation of famine, focusing on Somalia and taking note of the role of remittances, transnational social and economic networks, the consequences of de-risking, and the emergence of cash-transfers programs. Finally, I consider in more normative depth the transnational entitlement map of famine including: (i) transnational remittance networks (not national safety nets) ; (ii) global financial regulation (beyond international law) ; and (iii) diaspora politics (not democracy), where the parenthetic juxtapositions signal dissimilarities with current thinking about famine and global justice.